Thermophilic biohydrogen production from palm oil mill effluent: Effect of immobilized cells on granular activated carbon in fluidized bed reactor - Jamali, Nur Syakina; Dzul Rashidi, Nur Farahana; Md Jahim, Jamaliah; O-Thong, Sompong; Jehlee, Aminee; Engliman, Nurul Sakinah (Elsevier, 2019)
In this study, the performance of immobilized cells on granular activated carbon (GAC) for thermophilic biohydrogen production is determined using POME as a fermentation substrate. The immobilized cells are formed at different pH medium using sugar composition characterized in the POME. The pH 6 revealed the optimum pH used for biofilm development with HPR of 2.8 mmol H2/L h. The effect of sugar utilization by the immobilized cells on GAC are determined at different sugar concentration using the Monod model prior validated the performance of the cells in the fluidized bed reactor (FBR). From the model, 0.316 ± 0.013 h−1 of maximum specific growth rate was obtained at 20 g/L sugar used and was keep increasing to the maximum of 30 g/L of sugar used with HPR 2.6–2.8 mmol H2/L h. Lastly, the POME-enriched nutrients are used as the carbon source in the fluidized bed reactor (FBR). The highest HPR obtained was at HRT 12 h, (5.2 mmol H2/L h) and HY of 1.24 mol H2/mol sugar. The screening of the microbial population by DGGE revealed that the Thermoanaerobacterium thermosaccharolyticum sp. was dominant for all the HRTs, thereby indicating that this bacterium is resilient towards environmental disturbances.